2001
DOI: 10.1159/000045963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dilazep Dihydrochloride on Urinary Albumin Excretion in Patients with Autosomal Dominant Polycystic Kidney Disease

Abstract: Proteinuria and microalbuminuria occur with a highly variable severity and are associated with progression of autosomal dominant polycystic kidney disease (ADPKD). Dilazep dihydrochloride, an antiplatelet drug, is effective in patients with immunoglobulin A nephropathy or diabetic nephropathy. We studied whether dilazep dihydrochloride affects the urinary albumin excretion (UAE) in normotensive and hypertensive patients with ADPKD. Twelve normotensive ADPKD patients with microalbuminuria were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Although the mechanisms underlying the development and progression of diabetic nephropathy are not fully understood, platelet activation may participate by promoting microthrombus formation [21]. Recently, Yamagishi et al [22] reported that platelet activation plays a major role in the development and progression of rat diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms underlying the development and progression of diabetic nephropathy are not fully understood, platelet activation may participate by promoting microthrombus formation [21]. Recently, Yamagishi et al [22] reported that platelet activation plays a major role in the development and progression of rat diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Numabe et al [23] reported that treatment with dilazep through vascular and nonvascular effects maintains brain function in animals susceptible to vascular injury and organ dysfunction. Dilazep dihydrochloride is commonly used in patients with IgA nephropathy, ischaemic heart disease, polycystic kidney disease or diabetic nephropathy [8,21,24,25], and it is known to cause an increase in cerebral blood flow [6]. Dilazep dihydrochloride is reported to show the suppression of platelet adhesion and coagulation, the suppression of the platelet phospholipase activity, and maintenance of glomerular filtration rate due to increased renal blood flow [8].…”
Section: Discussionmentioning
confidence: 99%
“…Ten RCTs with 1,386 participants were included after assessment of 45 full-text articles and 197 records [ 1 8 , 10 15 ]. Electronic searching process was shown in the flowchart (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hypertension criteria in the studies was > 140/90 mm Hg. Two studies [ 6 , 15 ] divided patients into hypertension and normal BP groups.…”
Section: Resultsmentioning
confidence: 99%
“…19) Yoshida, et al 20) analyzed the relation between a reduction in proteinuria and renal histological findings in 46 patients with IgA nephropathy administered dilazep. In 18 patients whose proteinuria was reduced by more than 25%, the degrees of glomerular sclerosis, crescent formation, mesangial matrix, and tubulo-interstitial lesions were milder compared with those who had a persistently high proteinuria.…”
Section: Discussionmentioning
confidence: 99%